The role of news in promoting political disagreement on social media. (November 2015) - Barnidge, Matthew
Highlights: Network size and frequency of use are positively related to news use. News use is positively related to political messaging and monitoring. Messaging and monitoring are positively related to political disagreement. Messaging and monitoring mediate the relationship between news use and disagreement. Abstract: Determining whether and how social media networks expose individuals to political disagreement is critical to understanding how individuals experience civil society in the digital age. Recent research from the United States and Europe shows that, all else equal, heavy social media users are exposed to more political disagreement on social media than light users. The present study seeks to elaborate on these findings in the context of Colombia. In doing so, it adds depth to existing theory about social media and political disagreement by outlining a process for how social media use results in exposure to disagreement and the role played by news. Results from path analysis show that (a) news use on social media acts as a link between general use and disagreement and (b) political engagement mediates the relationship between news use and disagreement. Results are discussed in light of existing literature and possibilities for further research.